Elevated preoperative HMGB1 as predictor of myocardial injury post-percutaneous coronary intervention. Issue 46 (November 2016) - Jin, Peng; Zhou, Qi; Song, Shujiang; Xu, Jinpeng; Zhang, Minli; Zhu, Ming; Kang, Meili; Shi, Xiangming; Shi, Junting; Lu, Di; Li, Jing
Abstract : Abstract: In this study, we evaluated the impact of preoperative high mobility group box 1 (HMGB1) on myocardial injury post-percutaneous coronary intervention. We evaluated 302 consecutive patients who underwent percutaneous coronary intervention. They were divided into equal tertiles based on their preoperative HMGB1 levels. Creatine kinase-MB and troponin I levels were measured at baseline, 8- and 24-hours after the procedure, while clinical outcomes were followed up for 1 year. The occurrence of post-procedural myocardial injury was significantly higher in the tertile comprising of patients with elevated HMGB1 levels. Moreover, these patients showed significantly higher post-procedural peak values of creatine kinase-MB and troponin I in comparison to patients with lower HMGB1 levels. Event-free survival was significantly associated with HMGB1 levels, with worst event-free survival in patients with elevated HMGB1 levels. Elevated preoperative HMGB1 was a predictor of myocardial injury after percutaneous coronary intervention, and was associated with the worst clinical outcomes during 1-year follow up.